Analysis of Human Papillomavirus Genome Replication Using Two‐ and Three‐Dimensional Agarose Gel Electrophoresis. Issue 1 (16th May 2017) - Henno, Liisi; Tombak, Eva‐Maria; Geimanen, Jelizaveta; Orav, Marit; Ustav, Ene; Ustav, Mart
Abstract: This unit includes the necessary information to conduct neutral/neutral and neutral/alkaline two‐dimensional and neutral/neutral/alkaline three‐dimensional agarose gel electrophoresis. The methodology has been optimized over the years to gain a better outcome from the hard‐to‐interpret signals of human papilloma virus replication intermediates obtained from two‐ and three‐dimensional agarose gels. Examples of typical results and interpretation of replication intermediate patterns are included, and the outcomes of multiple‐dimension assays are assessed using previously published experimental data. © 2017 by John Wiley & Sons, Inc.